Diagnóstico do arranjo produtivo lácteo da microrregião de São Luís de Montes Belos, Goiás - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
An important instrument of regional development and competitiveness that has been promoted in Brazil in the last decade is the incentive to identify and consolidate so-called Local Productive Arrangements (APL’s). APL’s can be defined as territorial agglomerations of economic, political and social agents with a focus on a specific set of economic activities that present even incipient bonds. When interdependence, articulation, and consistent links are present among the agents, the APL’s are now considered as Local Productive and Innovative Systems (ASPLs). The development of the APL’s would have as objectives: i) the economic development; ii) reducing social and regional inequalities; iii) technological innovation; iv) expansion and modernization of the productive base; v) growth in the level of employment and income; vi) reducing the mortality rate of micro and small enterprises; (vii) increased schooling and training; (viii) increasing productivity and competitiveness; iv) the increase in exports. In Goiás, policies to support APL’s began in the year 2000. In 2009 there were 56 APL’s in the state, of which, of the 246 Goiás municipalities, 149 participated in at least one APL. The APL Dairy of the Region of São Luís de Montes Belos is one of the outstanding APL’s in the state. Located in the western region of Goiano, APL Dairy integrated 18 municipalities in 2005, and the articulation of its agents brought achievements in terms of interaction, cooperation and learning, aimed at promoting competitiveness and local development through milk production. Understand as it has the APL development process Milk the region of São Luís de Montes Belos could result in new shares proposition in research, assertiveness in proposing public policies and intervention strategies. All this in order to ensure the fulfillment of these needs and ensure future generations to meet their own needs through sustainability of their actions.
Keywords: Desenvolvimento local e regional; Arranjo produtivo local; Produção de leite; APL Lácteo; Local and Regional Development; Local Productive; Arrangement Milk Production; Dairy APL; CIENCIAS AGRARIAS